A Ceremony of Carols for Treble Voices and Harp, Op 28 (64 + 12 + 12 + 12) - Britten, Benjamin (Boosey & Hawkes, 1943)
Di dalam buku ini berisi: procession, wolcum yole!, there is no rose, that yonge child, balulalow, as dew in aprille, this little babe, interlude, in freezing winter night, spring caeol, deo gracias, recession, spring carol ( piano version).